Position of Women's Education in Accomplishing Sustainable Development Goals - Satrio Dwi Haryono; Syufi Astuti Muliyana (BUANA GENDER : Jurnal Studi Gender dan Anak, 2022)
This article aims to explain how the position of women's education towards the Sustainable Development Goals. The issue of gender equality in education needs to be addressed. The reason is that the role of humans in various lines of life cannot be represented by one gender alone. However, it is necessary to provide space and justice for other genders in various walks of life. Considering that education is one of the important variables in an effort to create a humane and just life. Although, in terms of quantity, education has found a point of equality. However, on the other hand, the quality is still far from equal. With that, it is necessary to rebuild equal and quality education on the basis that there is no dichotomy between the roles of women and men in various lines of life. The 17 goals of the Sustainable Development Goals will be played jointly by men and women.